2015
DOI: 10.1242/jeb.108449
|View full text |Cite
|
Sign up to set email alerts
|

The role of egg-nest contrast in the rejection of brood parasitic eggs

Abstract: Hosts of avian brood parasites can avoid the reproductive costs of raising genetically unrelated offspring by rejecting parasitic eggs. The perceptual cues and controls mediating parasitic egg discrimination and ejection are well studied: hosts are thought to use differences in egg color, brightness, maculation, size and shape to discriminate between their own and foreign eggs. Most theories of brood parasitism implicitly assume that the primary criteria to which hosts attend when discriminating eggs are diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 85 publications
(127 reference statements)
2
26
0
Order By: Relevance
“…1 ). However, as also seen in the American robin (Aidala et al 2015 ), egg-egg contrast is negatively correlated with egg-nest contrasts between experimental eggs and the natural nest lining's coloration (Fig. 1 ).…”
Section: Figsupporting
confidence: 61%
See 1 more Smart Citation
“…1 ). However, as also seen in the American robin (Aidala et al 2015 ), egg-egg contrast is negatively correlated with egg-nest contrasts between experimental eggs and the natural nest lining's coloration (Fig. 1 ).…”
Section: Figsupporting
confidence: 61%
“…To date, only one study has directly assessed whether avian perceivable egg-nest contrast per se is a proximate cause of foreign egg rejection by hosts of brood parasitic birds: Aidala et al ( 2015 ) found no causal relationship between egg-nest contrast and the rejection of red, blue (host mimetic), and beige (parasite mimetic) plaster eggs by American robins Turdus migratorius, an egg rejecter host of the generalist and non-mimetic brood parasitic brown-headed cowbirds Molothrus ater in North America (Croston and Hauber 2015b ). Parallel studies reported here have focused on the great reed warbler Acrocephalus arundinaceus, a commonly parasitized host of a highly mimetic host race of the common cuckoo Cuculus canorus in Hungary (Moskár) and elsewhere (Drobniak et al 2014 ).…”
Section: Figmentioning
confidence: 99%
“…If the nest was deemed abandoned (or deserted), eggs in the nest hatched, or the nest was depredated during the experimental period, the experimental trial was ended and excluded from the analyses. For a more detailed explanation of our experimental parasitism procedures on robins using plaster of Paris model eggs, see Croston and Hauber () and Aidala, Croston, Schwartz, Tong, and Hauber (). Critically, these studies found no effect of repeated parasitism and nesting stage (laying vs. incubation) on egg rejection rates by American robins.…”
Section: Methodsmentioning
confidence: 99%
“…For example, if hosts are able to recognize and reject cuckoo eggs, cuckoos may evolve eggs that mimic those of their hosts (Soler 2014). However, not all hosts of virulent cuckoos evolve egg rejection behavior (Kilner and Langmore 2011); some hosts seem to ignore a cuckoo's egg even when it is conspicuous against the background of their nest (Aidala et al 2015) or appears very different from their own eggs (Stoddard and Stevens 2011). Similarly, not all cuckoos have evolved mimetic eggs.…”
Section: Introductionmentioning
confidence: 99%